Corporate Environmental Responsibility: An Effort To Develop A Green Accounting Model - M. Wahyuddin Abdullah; Andi Yuliana (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
This study aims to detail environmental costs based on the relevance and accuracy of the information, and formulate a green accounting reporting model based on the characteristics of the company. Qualitative research uses a constructivism critical approach with PT Semen Tonasa in South Sulawesi as an analysis unit. Data collection is done by interview techniques and other secondary data support. The results showed that the company classifies environmental costs based on its activities and does not specify environmental costs, so the information is hidden and managers have difficulty controlling environmental costs. Environmental related costs are classified into environmental prevention costs, environmental detection costs, internal environmental failure costs, external environmental failure costs, and research and development costs. Presentation of environmental costs and disclosure of environmental activities contribute to maximum environmental performance. The formulation of the green accounting model is the fulfillment of environmental responsibility and the realization of accountability to stakeholders.